Dynamic state of atmosphere on the coast of Benin from radiosonde data of Cotonou - GUEDJE, KOSSI FRANÇOIS; HOUNGNINOU, BODOU ETIENNE; ADANMITONDE, Théophile; ADECHINAN, A. Joseph (My University, 2016)
This study characterizes the dynamic state of the atmosphere on the Coast of Benin from the radiosonde data. The average monthly wind speeds were calculated. The main results of this study provide information about the dynamics of the atmosphere through the jets characteristics. Two peaks were identified respectively around 5 km and 16 km altitude. The maximum value of the speed of the horizontal wind for the first jet is recorded in September with 17.5 m/s, whereas the same value is noted in July and is 23 m/s for the second jet. The rose corresponding wind at these levels for each study month was represented. This has allowed us to identify the prevailing wind in different months concerned. Then the vertical profiles of pressure, temperature and humidity have been shown.
Keywords: atmospheric dynamics; radiosonde; wind rose; atmospherics parameters